Patient Satisfaction Level and its Various Determinants in a Tertiary Care Hospital of Peshawar, Pakistan: A Cross-Sectional Study: Patient Satisfaction Level in a Tertiary Care Hospital - Wasim, Muhammad; Rehman, Khalid; Paracha, Majid; Sarfaraz, Junaid; Noor, Sahibzada Mahmood (Pakistan Journal of Health Sciences, 2025)
Patient satisfaction is a surrogate metric for quality of services provided by healthcare system. Objective: To assess patient satisfaction and associated factors in a major tertiary care hospital. Methods: This cross-sectional study was conducted at the Lady Reading Hospital (LRH), Peshawar, Pakistan. All patients admitted for indoor treatment for at least 2 days were enrolled through multistage sampling technique. Patients admitted to ICU, CCU, psychiatry or oncology wards and COVID-19 positivity were excluded. Patient satisfaction level was assessed with the Patient Satisfaction Questionnaire (PSQ)-18. Likert scale was utilized to evaluate patients’ response, where the scale ranged from 1 (complete dissatisfaction) to 5 (complete satisfaction). Patients with cumulative score of ≥ 50 were classified as satisfied. Results: Of the total 384 patients enrolled, 199 ( 52%) patients were older than 45 years of age, while the female to male ratio was 1.25:1. The number of satisfied patients was significantly higher than dissatisfied patients (313 vs. 71: p < 0.01). Highest number of patients were satisfied with the domain D7 (i.e., accessibility and convenience: 72%), followed by domain D6 (i.e., time spent with the doctor: 69%). A minimum number of patients were satisfied with the domain D2 (i.e., technical quality: 53%). Moreover, higher number of patients with age ≥45 years ( 86%), female gender ( 86%), with bachelor education ( 100%) and patient admitted to medical and allied wards ( 86%) expressed satisfaction. Conclusion: Overall, the study showed a high patient satisfaction at LRH, Peshawar.